2senx-1-cosx=0

Simple and best practice solution for 2senx-1-cosx=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2senx-1-cosx=0 equation:


Simplifying
2senx + -1 + -1cosx = 0

Reorder the terms:
-1 + -1cosx + 2ensx = 0

Solving
-1 + -1cosx + 2ensx = 0

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + -1cosx + 1 + 2ensx = 0 + 1

Reorder the terms:
-1 + 1 + -1cosx + 2ensx = 0 + 1

Combine like terms: -1 + 1 = 0
0 + -1cosx + 2ensx = 0 + 1
-1cosx + 2ensx = 0 + 1

Combine like terms: 0 + 1 = 1
-1cosx + 2ensx = 1

Add '-2ensx' to each side of the equation.
-1cosx + 2ensx + -2ensx = 1 + -2ensx

Combine like terms: 2ensx + -2ensx = 0
-1cosx + 0 = 1 + -2ensx
-1cosx = 1 + -2ensx

Divide each side by '-1osx'.
c = -1o-1s-1x-1 + 2eno-1

Simplifying
c = -1o-1s-1x-1 + 2eno-1

Reorder the terms:
c = 2eno-1 + -1o-1s-1x-1

See similar equations:

| -4(-6)+5= | | 2n+5n=0 | | 5k+13+5k=8k-19 | | 2g+6(5g-16)=5+19+20g | | 13/20x-15 | | 2senx-1+cosx=0 | | -5+p=9+3p | | 1/2(5x-8)=-9 | | 5m+4m=9 | | 15+15p=-9(-3p+13) | | -6h+5=-10-7h+9 | | -2(20h-18)-20h=3(-h-7) | | g=(x+7)(x+3) | | -12r+6(-16r-5)=-6(19r+19) | | 2(3x+4)=3(6x-5) | | 9+7j=4j | | X+5-2x=3+x | | x=2000000+0.333y | | 2x-24=82 | | -7-3n=-5n | | -7-2r=4+9r | | 2+4*5=30 | | -8=-3n+5n | | -6(-m-8)=-10m | | (2x-1)/3=(5x-6)/4 | | -10-7q=10-9q | | 11n-9=5n+45 | | 3(2r+14)=2(25+4) | | -9-9(13t-1)=6(-20t-10) | | 5n+22=22 | | 3(f-2)=7(f+2) | | C+5-2x=3+x |

Equations solver categories